Patient’s Natural Killer Cells in the Era of Targeted Therapies: Role for Tumor Killers - Messaoudene, Meriem; Frazao, Alexandra; Gavlovsky, Pierre Jean; Toubert, Antoine; Dulphy, Nicolas; Caignard, Anne (Frontiers in Immunology, 2017)
Natural Killer (NK) cells are potent anti-tumor effectors, involved in hematological malignancies and solid tumor immunosurveillance. They infiltrate various solid tumors and their numbers are correlated with good outcome. The function of NK cells extended their lytic capacities towards tumor cells expressing stress induced ligands, through secretion of immunoregulatory cytokines, and interactions with other immune cells. Altered NK cell function due to tumor immune escape is frequent in advanced tumors, however, strategies to release the function of NK infiltrating tumors are emerging. Recent therapies targeting oncogenic specific mutations improved the treatment of cancer patients, but patients often relapse. The actual development consists in combined therapeutic strategies including agents targeting the proliferation of tumor cells and others restorating functional anti-tumor immune effectors for efficient and durable efficacy of anti-cancer treatment. In that context, we discuss the recent results of the literature to propose some hypothesis concerning the potential use of NK cells, potent anti-tumor cytotoxic effectors, to design novel anti-tumor strategies.